Impact of social media and over the top media during COVID-19 lockdown, a cross-sectional study - Chebrolu, Raja Hirams; Janagam, Jayashree; Muraleedharan, K. C.; R., Resmy (International Journal Of Community Medicine And Public Health, 2021)
Background: Covid-19 outbreak has forced the governments of several countries to enforce lockdown to control the spread of the virus. Staying at their homes, people are subjected to use Social media (SM)/Over the top media (OTTM) for communication, information, and entertainment. The objective is to know the usage of SM/OTTM and the frequently used applications during the lockdown. Also, its association with health, information usage and education. Methods: An online survey was conducted for a month with a specially framed questionnaire which includes the aspects of SM/OTTM usage, health issues due to SM/OTTM usage, education, and information during Covid-19 lockdown. Results: Wilcoxon Signed-Rank test showed a significant difference between time spent on SM/OTTM before and after the lockdown and the median time used was shifted from 2-4 hours to 4-6 hours. Pearson Chi-Square test was done comparing the usage of SM/OTTM to other variables which showed significance in the aspects of interpersonal problems, usage out of boredom, staying connected to friends/family, online workouts/diet plans, false information, awareness on Covid-19, and cyberbullying. Sleeplessness, headache, eye complaints were predominant among the physical ailments whereas Stress, irritability, restlessness, anxiety were predominant among psychological affections due to SM/OTTM usage. Conclusions: SM/OTTM was frequently used and played a key role during the Covid-19 lockdown. SM has helped people to stay connected, acquire information, and stay updated on the pandemic. SM is also responsible for physical and mental health affections due to prolonged usage and exposure to false information during the lockdown.